Effect of Cow Dung, Biogas Slurry and Vermicompost on Phosphorus Adsorption Behavior of Soil - Seafatullah, M.; Hoque, M. A; Islam, M. S.; Islam, M. M.; Islam, M. N. (Journal of Scientific Research, 2015)
One of the approaches for phosphorus fertilizer management is controlling the soil phosphorus adsorption behavior. To examine the effect on phosphorus adsorption behavior, three amended soil samples were prepared by mixing 10% (w/w in dry basis) cow dung, biogas slurry and vermicompost with soil. Phosphorus adsorption behavior was examined by using Langmuir, and Temkin adsorption isotherms. Initially, biogas slurry and vermicompost increased the maximum phosphorus adsorption capacity (MPAC) of soil from 461 µg g-1 (control) to 558.0357 and 586.17 µg g-1 respectively, and then decreased steadily and reached 429.92 and 398.41 µg g-1 respectively in five weeks. Whereas in case of cow dung, MPAC was initially decreased, then reached maximum in 17 days and ultimately decreased. Thus application of cow dung along with phosphate fertilizer seems to increase the loss of the fertilizer through runoff and leaching. Conversely, biogas slurry and vermicompost prevent phosphorus loss by regulating phosphorus release through initial enhancement followed by gradual decrease in phosphorus adsorption capacity of soil. Both biogas slurry and vermicompost can be considered as good soil amendments as they have the ability to control the release of phosphorus fertilizer as per the need of the plants.